Longitudinal impacts of an online safety and health intervention for women experiencing intimate partner violence: randomized controlled trial - Marilyn Ford-Gilboe; Colleen Varcoe; Kelly Scott-Storey; Nancy Perrin; Judith Wuest; C. Nadine Wathen; James Case; Nancy Glass (BMC, 2020)
Abstract Background Responding to intimate partner violence (IPV) and its consequences is made complex by women's diverse needs, priorities and contexts. Tailored online IPV interventions that account for differences among women have potential to reduce barriers to support and improve key outcomes. Methods Double blind randomized controlled trial of 462 Canadian adult women who experienced recent IPV randomly were assigned to receive either a tailored, interactive online safety and health intervention (iCAN Plan 4 Safety) or a static, non-tailored version of this tool. Primary (depressive symptoms, PTSD symptoms) and secondary (helpfulness of safety actions, confidence in safety planning, mastery, social support, experiences of coercive control, and decisional conflict) outcomes were measured at baseline and 3, 6, and 12 months later via online surveys. Generalized Estimating Equations were used to test for differences in outcomes by study arm. Differential effects of the tailored intervention for 4 strata of women were examined using effect sizes. Exit survey process evaluation data were analyzed using descriptive statistics, t-tests and conventional content analysis. Results Women in both tailored and non-tailored groups improved over time on primary outcomes of depression (p < .001) and PTSD (p < .001) and on all secondary outcomes. Changes over time did not differ by study arm. Women in both groups reported high levels of benefit, safety and accessibility of the online interventions, with low risk of harm, although those completing the tailored intervention were more positive about fit and helpfulness. Importantly, the tailored intervention had greater positive effects for 4 groups of women, those: with children under 18 living at home; reporting more severe violence; living in medium-sized and large urban centers; and not living with a partner. Conclusion This trial extends evidence about the effectiveness of online safety and health interventions for women experiencing IPV to Canadian women and provides a contextualized understanding about intervention processes and effects useful for future refinement and scale up. The differential effects of the tailored intervention found for specific subgroups support the importance of attending to diverse contexts and needs. iCAN is a promising intervention that can complement resources available to Canadian women experiencing IPV. Trial registration Clinicaltrials.gov ID NCT02258841 (Prospectively Registered on Oct 2, 2014).